Upaya Strategi Brand Meyakinkan Konsumen dan Karyawan Pada UMKM: Studi Kasus Natto Milk Indonesia - Christine, Christine; Putri, Ahir Diana; Situmorang, Syafrizal Helmi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In the era of globalization, government development heavily relies on the economy. MSMEs are crucial for the advancement of a country, especially in its economic sector. MSMEs continue to grow year by year, even after the pandemic. However, MSMEs in the F&B sector face various challenges and intense competition, accompanied by changes in consumer behavior. MSMEs in Indonesia's food and beverage (F&B) sector must adopt effective branding strategies to differentiate themselves from competitors, win consumer hearts, and maintain employee loyalty. One such example is Natto Milk Indonesia. The strategic efforts to convince consumers and employees include product differentiation, storytelling-based communication through social media, and internal branding through employee training. These are the main strategies to convince both consumers and employees. The aim of this study is to provide a comprehensive overview of brand strategies for consumers and employees.